The circumscription of problematic species of Ophioglossum (Ophioglossaceae) from Southern South America: a palynological approach - Meza Torres, Esteban Ismael (2015)
The genus Ophioglossum has around 25 species with a nearly cosmopolitan distribution. It has historically posed a number of taxonomic problems due to the lack of morphological characters upon which to base species delimitations. In order to address this, we analyzed the sculpture patterns of spores from ten critical taxa from southern South America. Palynological data was compared with the morphology of the sporophyte. The sculpturing pattern was the most valuable and consistent taxonomic character upon which to base species delimitation in Ophioglossum. Nomenclatural types of studied species were examined. The name Ophioglossum melipillense is reinstated and the other species recognized to the genus Ophioglossum s.s. in this region are the following: O. crotalophoroides, O. nudicaule, O. opacum, and O. vulgatum. Ophioglossum fernandezianum appears to be a doubtful species. Ophioglossum lusitanicum is excluded from the study area, but the lectotype of O. lusitanicum is designated, and a revised synonymy is presented.